A monolithic anti-freezing hydro/organo Janus actuator with sensitivity to the polarity of solvents. Issue 61 (12th October 2018) - Fang, Chao; Yang, Kaixiang; Zhou, Qiang; Peng, Kang; Yang, Haiyang
Abstract : A monolithic anti-freezing hydro/organo Janus actuator which was synthesized by a one-step interfacial copolymerization shows various deformation patterns with solvent polarity. Abstract : Hydrogels with bilayer structures, known as actuators, have attracted increasing attention in recent years due to their sophisticated intellectual functions such as pine-cone-like bending and pod-like twisting in response to temperature, light, pH, special solvents etc. Herein, we synthesized a monolithic hydro/organic actuator by a direct one-step interfacial-incompatible polymerization of hydrophilic and hydrophobic vinyl macromolecular monomers, PEGMA and PPGMA, which were dissolved in water and ethyl acetate solutions, respectively. We found that the hydro/organo actuator exhibited directional, bidirectional, and site-specific bending behaviour under a single stimulus. In water and non-polar organic solvents, the hydro/organo actuator exhibited opposite bending behaviour as expected. However, in organic solvents, the hydro/organo actuator also exhibited quite different bending behaviour, depending on the polarity of the organic solvent. The hydro/organo actuator even experienced a dual responsive action in response to a single stimulus. We also found that such a hydro/organo actuator could be used effectively at low temperatures. The mechanism and potential applications of hydro/organo actuators based on PEGMA- b -PPGMA were also discussed and provided.